Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae) - Freyhof, Jörg; Kaya, Cüneyt; Turan, Davut; Geiger, Matthias (Zootaxa, 2019)
The Oxynoemacheilus tigris species group is reviewed, resulting in the recognition of six species, of which two are described herein as new. Oxynoemacheilus tigris is known from the endorheic Qweik River and the Merziman River, which is a tributary of the western Euphrates. Oxynoemacheilus ercisianus is endemic to the endorheic Lake Van basin and O. hazarensis is endemic to Lake Hazar basin in the upper Tigris drainage. Oxynoemacheilus kaynaki is widespread in the Euphrates drainage. The two undescribed species occur in the Euphrates drainage. Oxynoemacheilus arsaniasus, new species, from the Murat River and the upper Karasu (Muş) River drainage, is distinguished from other species of the O. tigris group by having a bold, black, irregularly-shaped bar at the caudal-fin base, an incomplete lateral line and a scaleless body. Oxynoemacheilus muefiti, new species, from the upper Murat River drainage and a tributary to the Atatürk reservoir, is most similar to O. ercisianus, from which it is distinguished by a more slender body and a shallower dorsal adipose crest. According to our molecular data, the Qweik population of O. tigris is suspected to be introgressed by O. namiri from the Orontes drainage. Oxynoemacheilus erdali is identified as a synonym of O. bergianus as we were unable to find differences between the two species.